Highly linear polarized emission at telecom bands in InAs/InP quantum dot-nanowires by geometry tailoring. Issue 40 (5th October 2021) - Jaffal, Ali; Regreny, Philippe; Patriarche, Gilles; Gendry, Michel; Chauvin, Nicolas
Abstract : A high degree of linear polarization (up to 91%) was achieved in telecom-band InAs/InP quantum dot-nanowires by geometry tailoring. Abstract : Nanowire (NW)-based opto-electronic devices require certain engineering in the NW geometry to realize polarized-dependent light sources and photodetectors. We present a growth procedure to produce InAs/InP quantum dot-nanowires (QD-NWs) with an elongated top-view cross-section relying on the vapor–liquid–solid method using molecular beam epitaxy. By interrupting the rotation of the sample during the radial growth sequence of the InP shell, hexagonal asymmetric (HA) NWs with long/short cross-section axes were obtained instead of the usual symmetrical shape. Polarization-resolved photoluminescence measurements have revealed a significant influence of the asymmetric shaped NWs on the InAs QD emission polarization with the photons being mainly polarized parallel to the NW long cross-section axis. A degree of linear polarization (DLP) up to 91% is obtained, being at the state of the art for the reported DLP values from QD-NWs. More importantly, the growth protocol herein is fully compatible with the current applications of HA NWs covering a wide range of devices such as polarized light emitting diodes and photodetectors.